In the light of what we know - Rahman, Zia Haider (London : Picador, 2015)
A bold, epic debut novel set during the war and financial crisis that defined the beginning of our century.
Originally published: 2014.
ENH
Keywords: Male friendship -- Fiction; Missing persons -- Fiction; Investment banking -- Fiction; English literature